Substance and individuation in Leibniz - Cover, J. A. (Jan A.), 1958- (Cambridge University Press, 1999)
This book offers a sustained re-evaluation of the most central and perplexing themes of Leibniz's metaphysics. In contrast to traditional assessments that view the metaphysics in terms of its place among post-Cartesian theories of the world, Jan Cover and John O'Leary-Hawthorne examine the question of how the scholastic themes which were Leibniz's inheritance figure - and are refigured - in his mature account of substance and individuation. From this emerges a sometimes surprising assessment of Leibniz's views on modality, the Identity of Indiscernibles, form as an internal law, and the complete-concept doctrine. As a rigorous philosophical treatment of a still-influential mediary between scholastic and modern metaphysics, this study will be of interest to historians of philosophy and contemporary metaphysicians alike.